2020
DOI: 10.1088/1757-899x/928/6/062004
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity of Winter Wheat Parts, Seed and Field Soil in Iraq, Basra Province

Abstract: This study was conducted to survey the fungal microflora in winter wheat (Triticum aestivum L.), ear, stem, root, seed and field soil in 17 field distributed on Basra province, Iraq. The mycoflora of plant parts, seeds and soil were determined morphologically and molecularly. In total 46 genera with 66 species of different fungal groups were found. The prevalent fungal group on all examined sources was the anamophic Ascomycota (85.34%), followed by Zygomycota (5.46%). Telemorphic Ascomycota was only at (3.64%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These results go hand in hand with those recorded in a previous study by Minati and Ameen (2020). Rostami et al (2016) assessed indoor and outdoor airborne fungi in an educational, research and treatment center.…”
Section: Isolation Distribution and Phenotypic Identification Of Yeastssupporting
confidence: 82%
“…These results go hand in hand with those recorded in a previous study by Minati and Ameen (2020). Rostami et al (2016) assessed indoor and outdoor airborne fungi in an educational, research and treatment center.…”
Section: Isolation Distribution and Phenotypic Identification Of Yeastssupporting
confidence: 82%
“…al., 2008). Closely related to the latter but not so scarcely present in the fungal studies, Botryotrichum was isolated from cucurbit plants (Huang et al, 2020), Rhizophora mangrove trees (Zhou & Xu, 2018), lianas (Bagchi & Banerjee, 2014), orchids like Cattleya species (Lizarazo-Medina et al, 2014), wheat rhizosphere in Iraq (Minati & Mohammed-Ameen, 2020), Eucalyptus spp. in Uruguay (Simeto et al, 2005) and cacao (Schmidt, 2012).…”
Section: Resultsmentioning
confidence: 94%
“…Another study by [14] isolated several fungi from the Eichhornia crassipes plant, four of which were predominant in the plant and GC-MS analysis indicated that they produced many bioactive compounds. In another study, Theilavia hyalocarpa was isolated with several pathogenic fungi from the winter wheat plant infected with head blight by less than 2% in Basra city [15]. The reason may due to the production of endophytic fungi for secondary metabolites, these fungi live with other microorganisms in the same host, forcing them to compete for nutrition, place and reproduction throughout their life cycle [16].…”
Section: Resultsmentioning
confidence: 99%